NANO-HYDROXYAPATITE AND HYDROXYCHAVICOL'S COMBINED EFFECT IN Streptococcus mutans GROWTH - Dewi, Nurdiana; Oktiani, Beta Widya; Tri Putri, Deby Kania; Amelia, Aura; Zahra, Aisyah Nur (Dentino: Jurnal Kedokteran Gigi, 2025)
Background: Early childhood caries is an aggressive form of dental caries that affects children under six years old. The increasing prevalence of ECC caused by Streptococcus mutans highlights the need for effective antimicrobial agents. Objective: To evaluate the antibacterial activity of a combination of nanohydroxyapatite (nHAp) and hydroxychavicol (HC) against S. mutans. Methods: 100 mg/mL nHAp was combined with HC at 0.125, 0.25, 0.5, and 1 mg/mL concentrations. DMSO 5% was used as the negative control. S. mutans ATCC 25175 was cultured in Brain Heart Infusion (BHI) media. Minimum Inhibitory Concentration (MIC) was determined using a UV-Vis spectrophotometer to measure absorbance differences. Minimum Bactericidal Concentration (MBC) was established by plating onto BHI agar and counting the colony count.  Results: The results showed that MIC occurred at a combination of nHAp 100 mg/mL + HC 0.125 mg/mL, while MBC was achieved at nHAp 100 mg/mL + 1 mg/mL HC, where no bacterial colonies were observed. Statistical analysis using ANOVA and Bonferroni post-hoc tests revealed significant differences in both absorbance reduction and colony counts between groups (p < 0.05), confirming the dose-dependent antibacterial efficacy of the nHAp-HC combination. Conclusion: These findings indicate that the synergistic action of nHAp and HC offers a promising strategy for controlling ECC, particularly by targeting the growth of S. mutans. Further, in vivo studies are recommended to explore clinical applicability and long-term safety.